Paus Leo XIV: Spiritualitas Agustinian dan Relevansinya bagi Gereja Masa Kini - Wicaksono, Agung (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
This article discusses the election of Pope Leo XIV (Robert Francis Prevost) as the 267th Pope of the Catholic Church, succeeding Pope Francis. His election is widely regarded as a sign of continuity with the pastoral and social vision of his predecessor. Drawing from his Augustinian background, cross-cultural experience, and a personal character marked by simplicity and contemplative depth, Pope Leo XIV brings renewed hope to the Church amid the complex challenges of the contemporary world. Through an engagement with the spirituality of Saint Augustine—particularly the themes of love, the civitas Dei, interior conversion, and the dialogue between faith and reason—this study argues that Pope Leo XIV embodies a form of leadership grounded in charity, unity, and profound reflection. In an increasingly fractured and noisy world, he calls the Church to become a community rooted in silence, animated by love, and open to sincere dialogue, so as to make the presence of God tangible within modern society.